Reducing Group Alignment in Factual Disputes? The Limited Effects of Social Identity Interventions. Issue 6 (December 2018) - Lyons, Benjamin
Public divisions over contested science often arise due to individuals' motivation to hold beliefs in line with others with whom they share a common social identity. To reduce the influence of threatened group identities, this research tests two potential interventions at the point of exposure to new information: self-affirmation and multiple identity salience manipulation. Experiments across dispute contexts—a toxic mining spill, a biofuels mandate, and gene editing technology—show limited support for either intervention reducing group alignment. Together, these results contribute to a growing body of work illuminating the limits of social identity interventions.